ANTUSIASME GURU DALAM PROGRAM PENGEMBANGAN KOMPETENSI PEDAGOGIK DAN DETERMINANNYA *) - Samuel, Donald (Universitas Kristen Satya Wacana, 2015)
This study aimed to describe the enthusiasm of the teachers at SMPN 2 Gedangsari, Gunung kidul in the program of Education and Training (Dik-lat) for pedagogic competence development, organized by the Education Foundation of Astra-Michael D. Ruslim (which is running a program of Corporate Social Responsibility in the field of education in the middleschool. In addition, this study also aimed to find the determinant factor for the enthusiasm of the teachers. This research applied mixed method. The results showed enthusiasm in participating in teacher training pedagogical competence development was quite high. In quantitative terms, the level of enthusiasm of teachers was worth on average 3.8 with H was rejected (teacher enthusiasm was high). In addition, there were several determinants affecting the enthusiasm of teachers, namely, the intensity of individual meetings (b value = 0.633), while the suitability of the teacher trainers approach did not affect the enthusiasm (b value = 0.364). Thus, the trainer advised to frequently meet with the teacher so that the enthusiasm of teachers increased, and dik-lat program targets could be achieved well. 0